Implementasi Kualitas Pelayanan untuk Meningkatkan Kepuasan Pelanggan di PT Pos Indonesia Cabang Sukabumi - Saori, Sopyan; Saftila, Diva; Hopia, Nida (Innovative: Journal Of Social Science Research, 2025)
This research discusses the implementation of service quality at PT Pos Indonesia Sukabumi Branch in improving customer satisfaction. The results show that aspects of service speed, staff friendliness, digitalization, and clarity of information are the main factors that influence customer satisfaction. The implementation of digital services, such as delivery tracking and online payments, provides convenience, although there are still challenges in customer technological literacy. In addition, constraints related to lack of information transparency and infrastructure limitations were also identified. By improving service quality in these areas, PT Pos Indonesia is expected to maintain customer loyalty and compete in an increasingly competitive logistics industry.